Online Star vs. Celebrity Endorsements: The Role of Self-Concept and Advertising Appeal in Influencing Purchase Intention - Shi, Pengfei; Lu, Xiaojing; Zhou, Yi; Sun, Chaojing; Wang, Liying; Geng, Biao (Frontiers in Psychology, 2021)
The booming Internet celebrity economy has led enterprises to increasingly value online star endorsements. Online stars are moving beyond promotions on social media to endorse products on multiple media platforms. However, few studies have addressed the effect of online star endorsement on consumers’ purchase intention. To address this gap in the field, this paper examines the effects of celebrity and online star endorsements on consumers’ purchase intention and aims to clarify the underlying mechanism and boundary conditions via comparison with the condition of no endorsement. The results of four studies revealed the following: (1) compared with no endorsement, both celebrity endorsement and online star endorsement led to increases in consumers’ purchase intention, with no significant difference between the two. (2) Self-concept is the mechanism that mediates these relationships; specifically, celebrity and online star endorsements activate the ideal and actual self, respectively, and enhance consumers’ willingness to purchase. (3) The effect of endorsements on consumers’ purchase intention is moderated by advertising appeals. That is, celebrity endorsement enhances purchase intention when consumers are exposed to symbolic appeals in advertisements, and online star endorsement enhances purchase intention when it is matched with functional appeals.